Agricultural Development and Economic Growth in Uganda: A Case Study of Rukiga District. - Ayebare, Joel (Kabale University, 2024)
The study explored the link between agricultural development and economic growth in Uganda, focusing on the Rukiga District. Using a case study research design, data was gathered through interviews and questionnaires. The findings highlighted that agricultural development contributes to economic growth through employment and income generation, poverty reduction, increased export earnings, rural development, infrastructure improvements, and market integration and value chain development. The study recommended encouraging farmers to diversify their crops to include drought-resistant varieties and alternative crops suited to the local climate and soil conditions. It also suggested promoting the cultivation of drought-tolerant crops like millet, sorghum, and cowpeas, which need less water and are more resilient to irregular rainfall patterns.